KONSEP DAN TEORI KURIKULUM SERTA PERENCANAAN KURIKULUM PAI DI SEKOLAH DAN MADRASAH: Abstrak, pendahuluan, metode penelitian, hasil penelitian dan pembahasan, kesimpulan, daftar pustaka - Amelia, Avi; A’la Nirotul Fikri; Eti Hadiati; Septuri; Ahmad Fauzan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the concepts and theories of curriculum and curriculum planning for Islamic Religious Education (PAI) in schools and madrasas in the context of implementing the Merdeka Curriculum. This research uses a qualitative approach with a literature study method, analyzing various relevant scientific sources. Data were collected through a review of 25 scientific articles from SINTA and DOAJ indexed journals published between 2015-2023, curriculum documents, and related books. The results show that the PAI curriculum in schools and madrasas is developed based on the same national curriculum foundation but with different emphasis and contextual approaches. In madrasas, the PAI curriculum is more intensive, comprehensive, and integrative with general subjects, while in schools, PAI tends to be a separate subject with limited hours. Curriculum planning for PAI must consider aspects of needs analysis, clear objectives, relevant content, appropriate methods, and comprehensive evaluation. The success of PAI curriculum planning is highly dependent on the competence of educators, availability of learning resources, and support from the school or madrasah environment. This research implies the need for a holistic and contextual approach in PAI curriculum planning to improve the quality of religious education in Indonesia